The Impact of Working Capital Management on the Profitability of Food Companies Listed on the Vietnam Stock Market - Uyen, Tran Tu; Oanh, Trieu Thi Hai (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 34 No 3, 2018)
Working capital management plays an important role in the operation of a business. To help better understand this, the study analyzes and evaluates the impact of working capital on the profitability of 56 food companies listed on the Vietnam stock market in the period 2015-2017 with the software EVIEWS 8.0. The results show an inverse relationship among the components of working capital management, including Inventory Turnover (INV), Average Receipt Period (AR), Average Payment Period (AP), cash conversion cycles (CCC), and return on assets (ROA). This finding is the basis to aid businesses in developing appropriate working capital policies to improve profitability.